Facilitators of and barriers to HPV vaccination among sexual and gender minority patients at a Boston community health center. Issue 26 (18th June 2018) - Apaydin, Kaan Z.; Fontenot, Holly B.; Shtasel, Derri; Dale, Sannisha K.; Borba, Christina P.C.; Lathan, Christopher S.; Panther, Lori; Mayer, Kenneth H.; Keuroghlian, Alex S.
Highlights: Knowledge, beliefs, engagement, and fear impact HPV vaccination among sexual and gender minorities. Providers' HPV knowledge and affirmation of sexual and gender minorities enable HPV vaccination. Inclusive healthcare settings, marketing, and public health campaigns may help HPV vaccination. Abstract: Background: Young sexual minority individuals have lower human papillomavirus (HPV) vaccine completion rates than the general population, and little is known about how gender minority people perceive HPV vaccination. The aim of this study was to qualitatively identify patient-, provider-, and systems-level barriers and facilitators for HPV vaccination among sexual and gender minority (SGM) people. Methods: Fifteen SGM-identified individuals, ages 23–26, were recruited at an urban community health center in Boston, MA, that specializes in care for SGM. Participants were enrolled in a study that utilized surveys and in-person focus groups. During focus groups, participants were asked to describe their perceived barriers and facilitators for completion of HPV vaccination. Results: Fourteen participants reported having a sexual minority identity, and five participants reported having a gender minority identity. Participants described the following factors influencing HPV vaccination: (1) at the patient level, low HPV-related knowledge and lack of engagement in care were associated with less vaccination, whereas fear of HPV-related disease motivated vaccination; (2) at the provider level, knowledge and SGM cultural-competence related to HPV was associated with patient willingness to be vaccinated; (3) at the systems level, SGM identity-affirming healthcare settings were associated with increased vaccination, whereas historical trends in HPV vaccine marketing selectively for cisgender women and lack of public awareness of HPV-related disease among SGM were associated with decreased vaccincation. Conclusion: Our study identified internal and external barriers for HPV vaccination related among SGM patients. These findings highlight the need to increase public awareness about the risks of HPV-related disease among SGM and educate SGM youth about HPV-related disease and vaccine importance. Finally, this study supports the need for future interventions to cultivate SGM-competent providers and SGM identity-affirming healthcare settings as a way to increase HPV vaccination.